Introduction of safety and quality standards for private health care providers: a case-study from the Republic of Srpska, Bosnia and Herzegovina - Severin Rakic; Budimka Novakovic; Sinisa Stevic; Jelena Niskanovic (BMC, 2018)
Abstract Background Regulation of private health care providers (PHPs) in middle-income countries can be challenging. Mandatory safety and quality standards for PHPs have been in place in the Republic of Srpska since 2012, but not all PHPs have adopted them yet. Adoption rates have differed among different types of providers. We studied three predominant types of PHPs to determine why the rate of adoption of the standards varies among them. Methods This study used a mixed methods approach, which allowed the integration of both quantitative and qualitative data, to develop an explanatory case study. The case study covered three types of private PHPs: pharmacies, dental practices and specialist practices. Primary data were collected through face-to-face semi-structured in-depth interviews and a self-administered postal survey of private health care providers. Our study's theoretical framework was based on the diffusion of innovation theory. Results The rate of adoption of mandatory standards varied among different types of PHP mainly due to four factors: (1) level of concern about negative financial consequences, such as the risk of fines or of losing contracts with the Health Insurance Fund of the Republic of Srpska; (2) availability of information on the standards and implementation process; (3) level of the relevant professional association's support for the introduction of standards; and (4) provider's perceptions of the relevant health chamber's attitude toward the standards. Opinions conveyed to PHPs by peers slightly negatively influenced adoption of the standards at the attitude-forming stage. Perceived gains in professional status did not have a major influence on the decision to adopt standards. All three types of PHPs perceived the same disadvantages of the introduction of safety and quality standards: associated expense, increased administrative burden and disruption of service provision. Conclusions When introducing mandatory quality and safety standards for PHPs, national health authorities need to: ensure adequate availability of information on the relative advantages of adhering to standards; support the introduction of standards with relevant incentives and penalties; and work in partnership with relevant professional associations and health chambers to get their buy-in for regulation of quality and safety of health services.